Auriculotherapy manual : Chinese and Western systems of ear acupuncture - Oleson, Terry; ScienceDirect eBooks (Edinburgh : Churchill Livingstone, 2013)
Auriculotherapy Manual: Chinese and Western Systems of Ear Acupuncture provides a comprehensive guide to the practice of Chinese and Western systems of ear acupuncture. This impressive new edition utilizes 3-D models of the external ear, as well as 3-D anatomical images, to demonstrate the somatotopic relationship between particular parts of the body and specific regions of the auricle. This is the first ear acupuncture text that has incorporated 3-D technology in order to present amazing images of the auricle which precisely indicate ear acupoint positions. The book offers in-depth evaluation of the theoretical and clinical underpinnings of auriculotherapy, describing and illustrating over 200 ear acupuncture points and more than 200 auriculotherapy treatment protocols for clinical discorders ranging from chronic pain to substance abuse to visceral and neurological disorders. There are an expanded number of auricular landmarks that are utilized to guide the practitioner in accurately determining the precise location of hidden ear points on the 3-D model. These landmarks further reveal the varied depth perspectives of the external ear. The ear reflex points presented in this manual are based upon systematic research conducted at the UCLA Pain Management Center and upon the extensive clinical findings of medical doctors and acupuncturists in China and Europe over the past 50 years. Scientific and clinical information from the most recent international symposia of auricular acupuncture have been used to update the scientific and clinical knowledge presented in this fourth edition. Each chapter is organized in same basic order, beginning with an introductory overview, progressing to the main topics in the chapter, and ending with a section listing a definition of terms and a set of preparatory sample questions. The book is concise and clear enough for students yet provides provides sophisticated clinical approaches to allow the experienced practitioner to enhance and complement their existing treatment strategies.
Includes bibliographical references and index.
Print version record.
Elsevier
Keywords: Ear -- Acupuncture; Acupuncture points; Acupuncture points; Ear -- Acupuncture; Electronic books